Renewable Polymers in Biomedical Applications: From the Bench to the Market - Lopes, Rauany Cristina (2024)
Polymers from renewable resources have been used for a long time in biomedical applications and play an irreplaceable role in some of them. Their uses have been increasing because of their attractive properties, contributing to improving life quality, mainly in drug release systems and in regenerative medicine. Formulations using natural polymers, nano, and microscale particles preparation, composites, blends, and chemical modification strategies have been used aiming to improve their properties for clinical application. Although many studies have been carried out with these natural polymers, the way to reach the market is long and only very few of them become commercially available. Vegetable cellulose, bacterial cellulose, chitosan, poly(lactic acid), and starch are the most studied polymers for biological applications, some with several derivatives already established in the market. In this scenario this work aims to describe the properties and potential of these renewable polymers for biomedical applications, the routes from the bench to the market, and the perspectives for future developments.